Interaction of the combustion of refuse derived fuel with the clinker bed in rotary cement kilns: A numerical study. (15th April 2020) - Pieper, C.; Liedmann, B.; Wirtz, S.; Scherer, V.; Bodendiek, N.; Schaefer, S.
Abstract: This paper presents CFD simulations of an industrial scale rotary kiln for cement clinker production. The fuel for the kiln flame is a mixture of pulverized coal and a Refuse Derived Fuel (RDF). Advanced models were developed to appropriately describe the thermal conversion characteristics and aerodynamics of non-spherical RDF particles. The models are based on detailed fuel analyses (e.g. flight and combustion characteristics, physical and chemical fuel properties) of major RDF fractions, like plastic foils, 3D plastic particles, paper & cardboard and textiles. The processes in the clinker within the kiln are approximated using a simplified one-dimensional model that calculates heat and mass exchange with the gas phase and the resulting chemical-mineralogical reactions in the solid bed. Calculation results of the one-dimensional model are compared to measurements obtained from a semi-industrial laboratory rotary kiln. Two cases, one with 100% lignite and one where 50% of the fuel heat input is substituted with RDF, are simulated. Based on the simulation results, the shift of flame shape and fuel conversion as well as the resulting effects on the clinker phase transition are analyzed and discussed. Results show that co-combustion of RDF can lead to lower gas and clinker temperatures in the sintering zone, which can affect the clinker properties.